Implementation Of Zoning System Policy In New Student Admissions In Bogor Regency, West Java - Wahman, Andri (Best Journal of Administration and Management, 2022)
Equality of education is one of the problems that occur in the education sector. The education equity program is one of the government's efforts in advancing education in Indonesia. One of them is the policy regarding PPDB, namely the zoning system. This zoning system was raised to realize educational equity and to remove favorite school brands in the community. With this system, it is expected that all schools will have the same quality and there are no favorite schools. With this policy, it is undeniable that problems arise both from the school as the implementer and the community, namely parents as education customers. The objectives of this study are 1) To find out how the implementation of zoning system policies in accepting new students, and 2) To find out how school stakeholders view zoning system policies. This research uses a qualitative approach, the type of research is descriptive using a case study design. For data collection techniques using Observation, Interviews, and Documentation. The results of this study revealed that four things in the implementation process, namely, Resources, Communication, Disposition, and Bureaucratic Structure have been done well enough so that they are carried out well. In addition, one of the supporters of policy implementation is community participation and can also be seen from the point of view of implementers and actors outside the government body.